Empowering Rural Farming: Agrovoltaic Applications for Sustainable Agriculture - Manish Kumar Singla; Jyoti Gupta; Anupma Gupta; Murodbek Safaraliev; Hamed Zeinoddini‐Meymand; Ramesh Kumar (Energy Science & Engineering)
ABSTRACT Agrovoltaics, also known as Agri‐PV or AV, is an innovative approach that entails the shared utilization of land for both the production of agricultural commodities and energy generation. This concept has gained immense popularity in recent times owing to its ability to boost income per unit of land area significantly. The scope of AV systems is quite extensive, as it encompasses solar energy converters and other renewable energy sources like bioenergy. Current strategies for agrovoltaic (AV) in agriculture are the outcome of the gradual development of agroecology and the integration of photovoltaic (PV) power supply into the grid. These approaches could lead to a nearly doubled income per unit area. Without on‐site power supply, reduced chemical fertilizers and pesticides, and on‐site yield processing, AV has the potential to revolutionize large‐scale unmanned precision agriculture and smart farming. These approaches might lead to significant changes in the logistics and value‐added production chain, thereby reducing agriculture's carbon footprint. In the future, it is possible to reduce the cost of AV technology by half by utilizing decommissioned solar panels in the technology and to delay the need for bulk PV recycling by several years. This review presents a different perspective to the common discourse on the topic, by giving special emphasis to the potential to further integrate AV into agriculture, which has the potential to facilitate the resolution of relevant legal disputes over the use of AV.